Chemical characterization of fine particulate matter, source apportionment and long-range transport clusters in Thohoyandou, South Africa - Novela, Rirhandzu J.; Gitari, Wilson M.; Chikoore, Hector; Molnar, Peter; Mudzielwana, Rabelani; Wichmann, Janine (Clean Air Journal, 2020)
This paper presents a chemical characterization of fine particulate matter in air masses passing through Thohoyandou and further determines their sources. Fine particulate matter (PM2.5) was collected and quantified using gravimetric method. X-ray fluorescence, Smoke stain reflectometer, Optical Transmissometer and Scanning Electron Microscopy- Energy Dispersive X-Ray Spectroscopy were used to determine the chemical and morphological composition of the particulate matter. The source apportionment was done using principal component analysis while the HYSPLIT model was used to depict the long-range transport clusters. The mean of concentrations of PM2.5, soot, black carbon and UVPM were 10.9 μg/m3, 0.69x10-5 m-1, 1.22 μg/m3 and 1.40 μg/m3, respectively. A total of 24 elements were detected in the PM2.5 with Pd, Sn, Sb, Mg, Al and Si being the dominant elements. SEM-EDS have shown the presence of irregular, flat and spherical particles which is associated with crustal material and industrial emissions. Source apportionment analysis revealed six major sources of PM2.5 in Thohoyandou namely, crustal materials, industrial emissions, vehicular emissions, urban emissions, fossil fuel combustion and fugitive-Pd. Air parcels that pass-through Thohoyandou were clustered into four. The major pathways were from the SW Indian Ocean, Atlantic Ocean and inland trajectories. Clusters from the ocean are associated with low concentration, while inland clusters are associated with high concentration of PM2.5. The PM2.5 occasionally exceeds the WHO daily guideline in Thohoyandou and the sources of PM2.5 extend beyond the borders. This study recommends that further studies need to be carried out to assess the health impacts of PM2.5 in Thohoyandou.